Answer:
10
Explanation:
X= 3
y= 5
2x² - y¹ + 3x⁰
You start by rewriting the question only substituting the unknown which is X and y with 3 and 5 respectively
Instead of writing X and y I am going to put (3) as X and (5) as y
2(3)² -(5)¹ + 3(3)⁰
You only square (²) the 3 and not the 2
If the question were like this: (2(3))² you'll square (²) both.
(3)² = 3×3 = 9
2(9) = 2×9= 18
18 - 5¹ + 3(3)⁰
5¹ = 5
Rule:
any number power 0 (⁰) is 1
any number power 1 (¹) is the number itself
18 - 5 + 3(1)
3(1) = 3×1 = 3
Finally rewriting the question in its simplest form:
18 - 5 + 3
when calculating we must follow an order of operations.
BODMAS is the abbreviation of;
Brackets
Of
Division
Multiplication
Addition
Subtraction
So according to the order of operation, we should by add then subtract.
5+3= 8
18 - 8= 10
the final answer is 10